High-quality low-dose cardiovascular computed tomography (CCT) in pediatric patients using a 64-slice scanner. (October 2018) - Cannaò, Paola Maria; Secchi, Francesco; Alì, Marco; D'Angelo, Ida Daniela; Scarabello, Marco; Di Leo, Giovanni; Sardanelli, Francesco
Background: Cardiovascular computed tomography (CCT) technology is rapidly advancing allowing to perform good quality examinations with a radiation dose as low as 1.2 mSv. However, latest generation scanners are not available in all centers. Purpose: To estimate radiation dose and image quality in pediatric CCT using a standard 64-slice scanner. Material and Methods: A total of 100 patients aged 6.9 ± 5.4 years (mean ± standard deviation) who underwent a 64-slice CCT scan using 80, 100, or 120 kVp, were retrospectively evaluated. Radiation effective dose was calculated on the basis of the dose length product. Two independent readers assessed the image quality through signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), and a qualitative score (3 = very good, 2 = good, 1 = poor). Non-parametric tests were used. Results: Fifty-five exams were not electrocardiographically (ECG) triggered, 20 had a prospective ECG triggering, and 25 had retrospective ECG triggering. The median effective dose was 1.3 mSv (interquartile range [IQR] = 0.8–2.7 mSv). Median SNR was 30.6 (IQR = 23.4–33.6) at 120 kVp, 29.4 (IQR = 23.7–34.8) at 100 kVp, and 24.7 (IQR = 19.4–34.3) at 80 kVp. Median CNR was 21.0 (IQR = 14.8–24.4), 19.1 (IQR = 15.6–23.9), and 25.3 (IQR = 19.4–33.4), respectively. Image quality was very good, good, and poor in 56, 39, and 5 patients, respectively. No significant differences were found among voltage groups for SNR ( P  = 0.486), CNR ( P  = 0.336), and subjective image quality ( P  = 0.296). The inter-observer reproducibility was almost perfect (κ = 0.880). Conclusion: High-quality pediatric CCT can be performed using a 64-slice scanner, with a radiation effective dose close to 2 mSv in about 50% of the cases.